Sediment properties, geochemical proxies, clay mineral composition and diatom assemblage of gravity cores obtained on the Drygalski Basin in the Ross Sea since Last Glacial Maximum - Ha, Sangbeom; Lee, Jae Il; Bak, Young-Suk; Yoo, Kyu-Cheul; Khim, Boo-Keun (PANGAEA, 2024)
For the reconstruction of paleoenvironment and retreat of grounding line and calving line, magnetic susceptibility, granulometry, biogenic opal, total organic carbon, d13C, total nitrogen, total organic carbon-total nitrogen ratio, CaCO3, clay mineral composition, diatom assemblage were analyzed. During the DG12 Expedition in 2012 using Korean I/B ARAON, gravity cores(DG12-GC01, GC02, GC04, and GC05) were obtained on the northern Drygalski Basin in the Ross Sea since Last Glacial Maximum.
Keywords: calving line; continental shelf; Drygalski Basin; Grounding Line; Ice Sheet; Ice shelf; Ross Sea; sediment